Unilateral Surgery for Medullary Thyroid Carcinoma: Seeking for Clinical Practice Guidelines - Zhang, Daqi; Colombo, Carla; Sun, Hui; Kim, Hoon Yub; Pino, Antonella; De Leo, Simone; Gazzano, Giacomo; Persani, Luca; Dionigi, Gianlorenzo; Fugazzola, Laura (Frontiers in Endocrinology, 2022)
Optimized preoperative diagnostic tools with calcitonin tests, ultrasound features, functional imaging modalities, and genetic testing to detect hereditary forms have led to an increased rate of earlier diagnosis and surgery for medullary thyroid cancer (MTC). This helps to adapt the primary surgery to the tumor stage and avoid surgical overtreatment for localized tumor growth, i.e., deviating from the regularly recommended thyroidectomy with bilateral central lymph node dissection in favor of a limited unilateral approach. To limit primary surgical therapy, it is crucial that the MTC is clinically unifocal, sporadic, and confined to the thyroid, and that calcitonin levels indicate biochemical recovery after surgery. The main requirement for such a limited approach is the availability of frozen section studies that reliably indicate (i) R0 resection of the MTC, (ii) absence of infiltration of the organ capsule, (iii) lack of desmoplasia (i.e., evidence of the metastatic potential of the MTC), (iiii) absence of contralateral disease or precancerous lesions. Informed consent is mandatory from the patient, who has been fully informed of the advantages, disadvantages, and potential risks of not undergoing the “classic” surgical procedure. The aim of this article is to review the guidelines for the management of early-stage MTC.